PENERAPAN MODEL RESEARCH BASED LEARNING (RBL) DENGAN PENDEKATAN SAINTIFIK DALAM PENINGKATAN PEMBELAJARAN IPS PADA SISWA KELAS V SDN 1 SUKOMULYO TAHUN AJARAN 2015/2016 OLEH: SILA RAMAHWATI1, MUH. CHAMDANI2, MOH. SALIMI3 PGSD FKIP UNIVERSITAS SEBELAS MA - Ramahwati, Sila (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Sila Rahmawati. The Application of Research Based Learning (RBL) Using Scientific Approach in Improving Social Science Learning in SDN 1 Sukomulyo in Academic Year 2015/2016. The objectives of this research are to describe the application of Research Based Learning using Scientific approach and to improve social science learning. This research is a collaborative Classroom Action Research (CAR). Validity of the data used in this research was the triangulation of sources and techniques. Analysis of data applied qualitative and quantitative data analysis. The results of this research were (1) the application of Research Based Learning models using scientific approach consists of a) Exposure Stage with observation, b) Lecturing of Core Knowledge with questioning, c) Experience Stage with gathering information, d) Internal Report Feedback with associating, e) Explanation of presentation, and f) Final report; (2) the application of Research Based Learning models using scientific approach can improve social science learning. Keywords: RBL, scientific approach, learning, social science Abstrak: Penerapan Model Research Based Learning (RBL) dengan Pendekatan Saintifik dalam Peningkatan Pembelajaran IPS Pada Siswa Kelas V SDN 1 Sukomulyo Tahun Ajaran 2015/2016. Tujuan penelitian ini adalah untuk mendeskripsikan penerapan model Research Based Learning dengan pendekatan Saintifik serta meningkatkan pembelajaran IPS. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) kolaboratif. Validitas data menggunakan triangulasi sumber dan teknik. Analisis data yang dipergunakan adalah analisis data kualitatif dan kuantitatif. Hasil penelitian ini adalah (1) penerapan model Research Based Learning dengan pendekatan Saintifik terdiri dari: a) Exposure Stage disertai observing, b) Lecturing of Core Knowledge disertai questioning, c) Experience Stage disertai mengumpulkan informasi/mencoba, d) Intern Report for Feedback disertai associating, e) presentation disertai mengkomunikasikan, f) Final report; (2) penerapan model Research Based Learning dengan pendekatan Saintifik dapat meningkatkan pembelajaran IPS. Kata Kunci: RBL, pendekatan saintifik, pembelajaran, IPS